Ivabradine and Milrinone—Bridge to Recovery in New HFrEF With Low-Output Heart Failure - Lekha Racharla; Lucas Gitzel; Max Joseph; Desire Guthier; Nael Hawwa (Case Reports in Cardiology)
In patients with newly diagnosed heart failure with reduced ejection fraction (HFrEF) who are on a downward clinical trajectory, options are mostly limited to left ventricular assist device and transplantation. However, in those with factors favorable for reverse remodeling, every effort should be made to promote native myocardial recovery. We present three patients with newly diagnosed severe HFrEF, NYHA Class 3–4 symptoms, and low cardiac output with and without organ malperfusion. Ivabradine and/or home milrinone were used during their tenuous hemodynamic period as a bridge to optimize guideline-directed medical therapy (GDMT), device therapy, and eventual reverse remodeling. Evidence of structural heart improvement continued far beyond 1 year.